Pro Gradu: Strategy work and strategic planning in Non-Profit Organizations in Finland - Kero, Anna-Leena (My University, 2024)
In today's rapidly evolving business environment, all types of organizations are challenged in multiple ways. The significance of planning and strategizing becomes particularly important in this volatile environment. Strategic planning does not only guide an organization's activities, but also serves as an essential management tool and steers the organization. Studies have shown that well-formulated strategic decisions are strongly linked to achieving successful business outcomes. The aim of this study is to examine strategic work and strategic thinking within the context of non-profit organizations. In Finland, the activities of non-profit organizations are governed by the Associations Act, which establishes important boundaries for organizational planning. Unlike profit-driven entities, non-profit organizations must primarily focus on fulfilling their social mission rather than pursuing financial gain. Also, the financial base and organizational structure of these types of organizations typically differ from those of for-profit organizations. The study was conducted as qualitative research by interviewing 5 selected non-profit organization leaders during the spring and summer of 2022. The data was gathered through semi-structured interviews, and the data processing was carried out using a coding method, resulting in four overarching categories that summarize the conclusions of the interviews in relation to the research question The study findings suggest that strategy is considered an important element in non-profit organ- izations, especially as a management tool and a key aspect of organizational development. Findings also suggest that strategic planning in these organizations is conducted via a systematic process, with a strong emphasis on involving and considering various stakeholders throughout the planning process. The limitations of this study is the small sample size of organizations studied, which prevents making broad generalizations about strategic planning and practices in non-profit organizations. However, the findings of this study do provide additional insights into strategic research from the perspective of non-profit organizations that operate under specific legal constraints and possess a distinctive organizational structure and financial base.
Keywords: leadership (activity); strategic planning; strategic leadership; strategies; corporate strategies; associations; non-profit corporations; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development